Highly Active Bio-Waste Cellulose Supported Poly(Amidoxime) Palladium(II) Complex for Heck Reactions - Islam, Md. Shaharul; Lutfor, M. R.; M. M., Yusoff; Sarkar, Shaheen M. (Elsevier, 2017)
Corn-cob cellulose supported poly(amidoxime) Pd(II) complex was synthesized and characterized by field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HR-TEM), energy dispersive X-ray (EDX), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and inductively coupled plasma atomic emission spectroscopy (ICP-AES) analyses. The cellulose supported heterogeneous Pd(II) complex showed high stability and catalytic activity towards Mizoroki-Heck reaction of aryl halides and arenediazonium tetrafluoroborate with a variety of olefins to give the corresponding cross-coupling products in up to 97% yield. The Pd(II) complex was separated from the reaction mixtures and repeatedly used up to seven times without any significant decrease of its catalytic performance.